Coaches` perceptions of common planning concepts within training theory: An international survey - Anyadike-Danes, K.; Donath, L.; Kiely, J. (Sports Medicine - Open, 2023)
Many coaches, even self-described periodisation users, did not employ key periodisation concepts such as training specific fitness factors in a sequential order.